Politique de sécurité et villages-frontière entre États-Unis et Québec - Frédéric Lasserre (Unité Mixte de Recherche 8504 Géographie-cités, 2012)
The Canada-US border crosses several villages in its Quebec segment. A few buildings are even built astride the border. The local residents are now used to the peculiarities of the situation, even encouraging it while fostering a solid social and institutional cooperation. This odd situation creates many administrative problems for the residents, all the more so since September 11, 2001. The theoretical debate about artificial boundaries resurfaced among this sudden strengthening of border controls and the reaction among the locals. It would be more accurate to stress border management practices as the core factor for this complex situation.